Dietary Factors for Premature Skin Aging in Adult Students of the Faculty of Medicine, YARSI University, Class of 2021 Reviewed From Medicine and Islam - Ayuning Tasyqiya Syahrani (Jurnal Indonesia Sosial Teknologi, 2024)
Premature Skin Aging is a change in the skin that occurs as a result of the aging process. The occurrence of aging on the skin is based on the physiological aging process of the organs, which can ultimately cause skin aging. The main factor causing premature skin aging is lifestyle, one of which comes from nutrition. This research uses a quantitative research method and a cross-sectional analytical observation method. The population used in this research were individuals studying at the Faculty of Medicine, YARSI University, class of 2021, with the age group 20-25 years. The sampling technique used in this research is a purpose sampling technique. From the existing population, 20 students were taken as samples. The type of data used in this research is primary data. The data analysis technique used in this research is the Chi-Square Test. This research found that the average sample of students at the Faculty of Medicine, Yarsi University class of 2021, had a suitable and sufficient diet. Ten students (50%) had an adequate diet, and the other 10 (50%) had a good diet. Hypothesis testing using the Chi-Square test produces Asymp values. Sig. (2-sided) of 0.037, this value is smaller than 0.05 (0.037 < 0.05), so H1 is accepted. The conclusion is that there is an influence between diet and the process of premature skin aging